5 - A ‘Chinese’ Street (Un)Scripted and (Re)Imagined: Material Shifts, City-Making and Altered Ways of Living in Suburban Johannesburg - Dittgen, Romain; Chungu, Gerald; Lewis, Mark (Africa Development, 2023)
Derrick Avenue in Cyrildene, is a striking example of clichéd Chinese (street life) atmosphere in Johannesburg. Owing to its visible markers and demographics, this activity node sparks visions of a spatialised elsewhere. Standing in sharp contrast to a surrounding quiet and mostly residential neighbourhood, Derrick Avenue has been viewed as exceptional, different and closed, resulting in a spatial and cognitive divorce from the rest of the area. These representations, largely associated with Chinese spaces, not only shape the ways in which such spaces are commonly examined, understood and conceptualised, but also contribute to side-lining the existence of transversal urban processes and realities. This article moves away from entering Derrick Avenue through the lens of ethnicity and othering, in an effort to read this street as a holistic object of research. Through (un)writing this space, we unpack its complexities as well as explore the coexistent tension between specific characteristics of a lived and constructed differentiation and geographies of the ‘familiar’ Once decoupled from predetermined analytical categories and conceptual frameworks, the articulation between ‘migrant space’ and ‘host city’ is not merely confined to a study of relational ties (whether parallel, contentious or complementary), but becomes one of entanglement in terms of city-making processes and broader societal dynamics.